Developing Symbolic Interpretation Through Literary Argumentation. Issue 1 (2nd January 2016) - Sosa, Teresa; Hall, Allison H.; Goldman, Susan R.; Lee, Carol D.
Abstract : Literature can be a powerful resource for adolescents' psychosocial development, as it provides opportunities to experience the world through the perspectives of others and juxtapose these with one's own experiences. However, gaining access to these perspectives requires going beyond literal words on the page to explore interpretive meanings. This mixed-methods case study addresses the need to better understand how adolescent students learn to interpret literary works. Specifically, 9th-grade students participated in a 5-week instructional module focused on symbolic interpretation and coming of age themes in texts with a variety of sources of complexity. The primary data sources were an intentional sample of classroom discussions and essays written before and after instruction. Analyses indicate that students learned to make interpretive claims around symbolism. Textual evidence to support these claims was evident in whole-class discussions but less so in the written essays. Students also struggled to reason about why evidence supported particular claims and how the interpretive claims were related to understanding the characters and their worlds. Discussion focuses on the value of symbolic interpretation as a starting point for engaging adolescents in interpretive practices but notes that developing facility with literary interpretation takes concerted effort over longer periods of time.